Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Kopi Keliling di Lombok: Pendekatan Theory of Planned Behavior - FAHRUL HUDATIL ATKIYAN (Business Management, 2026)
The increasing development of the MSME sector has led to the emergence of new innovations from the community. The phenomenon of mobile coffee vendors is one tangible example of the increasingly modern development of MSMEs. On the island of Lombok, the growth of mobile coffee, especially in the city of Mataram, has become a widespread phenomenon. Many mobile coffee brands have emerged, with their numbers even reaching dozens of brands. The variety of mobile coffee products is the main foundation of this research. With the diversity of mobile coffee products that have emerged, this study then attempts to examine the factors that can influence consumer purchasing decisions for mobile coffee products. Using the lens of the theory of planned behavior and adding the brand image variable, the results show that there are two factors that influence consumer purchasing decisions, namely attitude and brand image.